Manipulative Dominant Discoursing: - Debbie Garratt; Joanna Patching (Grounded Theory Review: An International Journal)
This paper is a grounded theory explaining the main concern of practitioners in Australia when interacting with women on the issue of abortion. Based on a broad data set including practitioner interviews, professional notes, and discourse data, collection and analysis were undertaken using Classic Grounded Theory research design. The analysis led to the development of the grounded theory, Manipulative Dominant Discoursing: Alarmist Recruitment and Perspective Gatekeeping.